Trends in use of hydroxychloroquine during pregnancy in systemic lupus erythematosus patients from 2001 to 2015. (May 2018) - Bermas, B L; Kim, S C; Huybrechts, K; Mogun, H; Hernandez-Diaz, S; Bateman, B T; Desai, R J
Background: Evidence suggests that continuing hydroxychloroquine (HCQ) during pregnancy in women with systemic lupus erythematosus (SLE) improves outcomes. We sought to describe time trends in the continuation, initiation, and duration of HCQ in a large population-based cohort of pregnant SLE women. Methods: A cohort of pregnant women with SLE enrolled continuously in public (Medicaid, 2001–2010) or private (Optum Clinformatics, 2003–2015) health insurance between three months prior to conception and one month after delivery was identified. We assessed the proportion of women initiating or continuing HCQ and the duration of therapy during each calendar year in the study. Results: A total of 5300 women with SLE were included. Of these, 852 (16.1%) were on HCQ treatment in the three-month period prior to their pregnancy. During pregnancy, the overall proportion of women with SLE taking HCQ increased from 12.4% in 2001 to 37.7% in 2015. Initiation of HCQ therapy during pregnancy increased from 2.7% in 2001 to 7.5% in 2010 (  p  = 0.0002) (Medicaid) and from 4.9% in 2003 to 13.6% in 2015 (  p  = 0.0001) (Clinformatics). Continuation of HCQ during pregnancy did not change significantly over time in either data set. The average cumulative day-supply of HCQ prescriptions during pregnancy increased from 37 days in 2001 to 77 days in 2010 (  p  = 0.05) among HCQ initiators and from 79 days in 2001 to 125 days in 2010 (  p  = 0.0009) among HCQ continuers in Medicaid. Among privately insured women, the average cumulative day-supply of HCQ prescriptions among HCQ continuers increased from 84 in 2004 to 163 in 2015 (  p  = 0.0006) but did not change significantly among HCQ initiators. Conclusion: The proportion of women initiating HCQ during pregnancy and the average cumulative day-supply of HCQ increased from 2001 to 2015. While these findings are encouraging, overall HCQ use during pregnancy remains low.